2017
DOI: 10.3390/ijms18020413
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Pentoxifylline on the Development of Colonic Premalignant Lesions in Obese and Diabetic Mice

Abstract: Obesity and its related metabolic abnormalities, including enhanced oxidative stress and chronic inflammation, are closely related to colorectal tumorigenesis. Pentoxifylline (PTX), a methylxanthine derivative, has been reported to suppress the production of tumor necrosis factor (TNF)-α and possess anti-inflammatory properties. The present study investigated the effects of PTX on the development of carcinogen-induced colorectal premalignant lesions in obese and diabetic mice. Male C57BL/KsJ-db/db mice, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Previously, it was reported that diet-or drug-induced diabetic and obese mice were significantly susceptible to colon tumorigenesis in carcinogen-induced colon cancer models (12,13). In addition, recent studies have revealed that several types of natural compounds and medicines, including catechins obtained from green tea, curcumin, and pentoxifylline suppressed the development of diabetesand obesity-related colorectal tumorigenesis partially by attenuating chronic inflammation (14)(15)(16). These findings indicated that diabetes-and obesity-associated metabolic abnormalities may be important targets for preventing colon cancer development in diabetic and/or obese individuals (10).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that diet-or drug-induced diabetic and obese mice were significantly susceptible to colon tumorigenesis in carcinogen-induced colon cancer models (12,13). In addition, recent studies have revealed that several types of natural compounds and medicines, including catechins obtained from green tea, curcumin, and pentoxifylline suppressed the development of diabetesand obesity-related colorectal tumorigenesis partially by attenuating chronic inflammation (14)(15)(16). These findings indicated that diabetes-and obesity-associated metabolic abnormalities may be important targets for preventing colon cancer development in diabetic and/or obese individuals (10).…”
Section: Introductionmentioning
confidence: 99%
“…Among the candidates for CRC chemoprevention, COX-2 inhibitors, 5-ASA, and certain types of phytochemicals, such as green tea catechins, which possess anti-inflammatory and anti-oxidant effects, have shown promising results [ 26 28 ]. In this study, we focused on evaluating the effectiveness of PTX against CRC development, because it is reported to have anti-cancer activities besides being anti-inflammatory [ 10 , 13 , 29 ]. Moreover, because this compound has already been used as a drug, the feasibility of its clinical application is already established [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are important, because the increased level of COX-2 contributes to the development of CRC; therefore, targeting this molecule can be an effective strategy for chemoprevention of CRC [ 31 , 32 ]. Using several colorectal carcinogenesis models, various agents, including COX-2 inhibitors, have been reported to inhibit the expression of COX-2, leading to the suppression of CRC development [ 13 , 22 , 28 , 33 ]. In our study, PTX inhibited the expression of COX-2 in the colonic mucosa, which probably led to the suppression of colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branched-chain amino acid (BCAA) supplements, containing essential amino acids such as leucine, isoleucine, and valine could alleviate protein malnutrition and exert anti-cancer properties by ameliorating insulin resistance [ 22 ]. Pharmaceutical approaches using the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor pitavastatin, anti-hypertensive drugs, histamine receptor antagonists, and an anti-inflammatory agent pentoxifylline have been investigated and reported to attenuate chronic inflammation and reduce oxidative stress, leading to the prevention of colonic neoplastic lesion development [ 17 , 20 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%